Solvent-free microwave synthesis of ultra-small Ru-Mo2C@CNT with strong metal-support interaction for industrial hydrogen evolution - Xueke Wu (Nature Portfolio, 2021)
While H2 could be a renewable fuel, the large-scale preparation of cheap, active electrocatalysts for large-scale production remains a challenge. Here, authors use a rapid, solvent-free microwave pyrolysis method to synthesize nanostructured catalysts for large-scale industrial H2 production.